Validation of the Donkey Pain Scale (DOPS) for Assessing Postoperative Pain in Donkeys - Oliveira, Maria Gláucia Carlos de; Paula, Valéria Veras de; Mouta, Andressa Nunes; Lima, Isabelle de Oliveira; Macêdo, Luã Barbalho de; Nunes, Talyta Lins; Trindade, Pedro Henrique Esteves; Luna, Stelio Pacca Loureiro (Frontiers in Veterinary Science, 2021)
This study aimed to validate a scale for assessing acute pain in donkeys. Forty-four adult donkeys underwent castration after sedation with intravenous (IV) xylazine, induction with guaifenesin and thiopental IV, local anesthetic block, and maintenance with isoflurane. The scale was constructed from a pilot study with four animals combined with algetic behaviors described for equines. After content validation, the scale was evaluated in other 40 donkeys by three blinded and one reference evaluator, by means of edited videos referring to the preoperative and postoperative periods: before anesthesia, three to four hours after recovery from anesthesia, 5-6 hours after recovery from anesthesia (2 hours after analgesia with flunixin - 1.1 mg/kg, dipyrone - 10 mg/kg, and morphine - 0.2 mg/kg) IV, and 24 hours after recovery. Content validity, sensitivity, specificity, and responsiveness of behaviors were investigated to refine the scale. Intra- and inter-evaluator reliabilities were investigated by the weighted kappa coefficient, criterion validity by comparing the scale with the visual analogue scale (VAS), internal consistency by Cronbach's α coefficient, item-total correlation by the Spearman coefficient, and intervention point for rescue analgesic by the receiver operating characteristics curve and Youden index. The scale showed very good intra-evaluator reliability (0.88 – 0.96), good to moderate (0.56 – 0.66) inter-evaluator reliability, responsiveness for all items, good criterion validity vs. VAS (0.75), acceptable internal consistency (0.64), adequate item-total correlation, except for head position and direction, and according to the principal component analysis, good association among items. The accuracy of the point for rescue analgesic was excellent (area under the curve = 0.91). The rescue analgesic score was ≥ 4 of 11 points. The scale can diagnose and quantify acute pain in donkeys submitted to castration, as the instrument is reliable and valid, with a defined intervention analgesic score.